Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas Dan Capital Intensity Terhadap Agresivitas Pajak Dengan Kualitas Audit Sebagai Pemoderasi: Studi pada Sektor Energi Perusahaan Terbuka tahun 2017-2021 - Ivahtun Nurhayati; Syahril Djaddang; Sailendra (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to examine the effect of firm size, profitability, liquidity, and capital intensity on tax aggressiveness with audit quality as a moderator. Tax aggressiveness was measured using the long-run cash effective tax rate (LR CETR). The research was conducted in the public company energy sector for the period 2017-2021 using a quantitative approach with a purposive sampling method. The data analysis method in this study uses a structural equation model (SEM) approach based on partial least squares (PLS). The results of the study show that firm size, profitability, and liquidity have an effect on tax aggressiveness, and capital intensity has no effect on tax aggressiveness. Audit quality is proven to moderate the effect of company size and profitability on tax aggressiveness. The results of this study are expected to be of use to the Government through the DGT in formulating a tax strategy in order to mitigate tax aggressiveness by companies as a mandatory tax and to improve the gaps in the current tax regulations and can be used as a reference for further research